De Félix Martin-Sabon à Pierre Pradel, une histoire de plaques de verre - Anne-Bénédicte Mérel-Brandenburg (Les Cahiers de l'École du Louvre)
The École du Louvre holds, in the spaces of its photographic library, an iconographic collection made up of photographs, postcards, positive and negative glass plates in various sizes, black and white, autochromes, celluloid negatives and slides, supplanted by digital in 1995. Beyond the patrimonialisation of this exceptional collection intended for teaching, the article will focus, based on written archives put into perspective with the glass-plate collection, on its peregrinations (1932–2005), genesis and constitution, management and classification (1900–60), and the renewed interest in the 2010s. The richness of the corpus thus offers new objects of study, from the history of photography to a multidisciplinary approach: painting, sculpture, decorative arts, archaeology, museology and pedagogy.